SISTEM PAKAR PENYAKIT PADA ITIK BERBASIS WEB (Information Technology and Telematics, 2013)
In the world of farming is not spared from disease problems faced by farmers, if not handled properly, could cause harm to farmers  whose numbers can be very large and bankruptcy.                 Expert system for web-based disease ducks contains knowledge needed by farmers to overcome the existing problems. To the knowledge base in this system using data collection techniques are interviews, observation, study the literature, and documentation. For inference methods used in building expert systems are forward chaining method. Software development methodology using structured methods of Data Flow Diagrams (DFD) and Entity Relationship Diagram (ERD). Software used to build this expert system is Adobe Dreamweaver CS5 using MySQL database.                The purpose of this system is to facilitate farmer download for Ducks diagnosis of a disease. In the design of this system the user just simply choose what symptoms experienced by the ducks later in the process after the results (output) will appear on the screen in the form of solutions, prevention, treatment and accompanied by pictures. Keywords:  Expert System, Forward Chaining, PHP, MySQL,  Ducks Disease.